Editorial - Mishra, Sanjay Kumar (Cognition, 2026)
It is with immense pleasure that we present Volume 8, Issue 1 (January 2026) of COGNITION, a peer-reviewed transdisciplinary research journal published by the National University Teachers’ Association, Patan Multiple Campus, Tribhuvan University. Since its inception, COGNITION has remained committed to fostering rigorous scholarship, intellectual plurality, and meaningful dialogue across disciplines, and this issue stands as a strong testament to that mission.